COVID-19 and the Irish welfare system - Claire Keane; Karina Doorley; Dora Tuda (The Economic and Social Research Institute (ESRI), 2021)
COVID-19 had, and continues to have, a strong negative effect on incomes in Ireland due to widespread job losses as the measures put in place to slow the spread of the disease resulted in severe economic restrictions. Despite the existence of unemployment supports, additional income supports were introduced to protect incomes. As public health restrictions lift and the economy recovers, we face the withdrawal of such supports. We examine these supports and the role they played in supporting incomes. By profiling those who benefitted most from the new schemes, we highlight the groups most at risk of significant income losses as they wind down. We consider what gaps in the social welfare system necessitated the introduction of such schemes in the first place, along with potential future policy changes to ensure that the social welfare system can provide adequate income protection and financial incentives to work as we emerge from the COVID-19 crisis.
Keywords: 330; Coronavirus; Öffentliche Sozialleistungen; Arbeitslosigkeit; Irland